2014
DOI: 10.1016/j.toxrep.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary feeding of flavokawain A, a Kava chalcone, exhibits a satisfactory safety profile and its association with enhancement of phase II enzymes in mice

Abstract: Flavokawain A (FKA), a major chalcone in the Kava plant, has recently demonstrated promising anti-cancer activities. A systematic evaluation of FKA's safety profile has not been reported before. In this study, male FVB/N mice were fed with an AIN-76A diet or AIN-76A diet supplemented with 0.6% (6 g/kg food) FKA or 0.6% commercial kava root extract (KRE) for three weeks. Dietary feeding of FKA did not affect food consumption and body weight. Histopathological examination of liver, kidney, colon, lung, heart, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Therefore, kava extracts as beverage have been increasingly developed and used to prevent bladder cancer owing to its low toxicity (Li et al, 2014). However, there were reported cases of hepatotoxicity using commercial kava root extracts (Teschke, 2010;Teschke and Wolff, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, kava extracts as beverage have been increasingly developed and used to prevent bladder cancer owing to its low toxicity (Li et al, 2014). However, there were reported cases of hepatotoxicity using commercial kava root extracts (Teschke, 2010;Teschke and Wolff, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An enhancement of those enzymatic activities is considered to be beneficial for health since it means that the carcinogen excretion is also enhanced. This effect is correlated with a protection against chemically induced tumours as it is demonstrated in many studies (Li et al, 2014;Sangeetha, Viswanathan, Balasubramanian, & Nalini, 2012). For example, Vinothkumar et al (2014) showed that the supplementation of increasing doses of troxerutin ranging from 12.5 to 50 mg/kg was able to induce significantly (p < 0.05) the activities of phase II enzymes such as GST, DTD and UDPGD in DMH treated rats.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, Herceptin plus FKA treatment led to enhanced inhibitory effects on the growth of HER2 overexpressing breast cancer cells. These results indicates that FKA with excellent safety profile [18,21] deserves further investigation for its potential use as an adjuvant agent in combination with Herceptin for treatment of HER2 positive breast cancer or as a preventative agent for targeting HER2 positive early breast cancer in preventing its recurrence and progression.…”
Section: Discussionmentioning
confidence: 85%
“…We have further demonstrated that FKA is a novel neddylation inhibitor and causes degradation of Skp2 protein [18,20]. Dietary feeding of FKA inhibits tumorigenesis in the mouse transgenic models of bladder and prostate carcinogenesis without exhibiting any adverse effects on major organ function (including liver function) and homoeostasis in mice [18,[20][21][22]. However, the effect of FKA on HER2 overexpressing breast cancer has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%